2022
DOI: 10.1039/d2tb00735e
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized nanocomposite hydrogel mechanically reinforced by polyelectrolyte-modified nanoparticles

Abstract: Vascularization plays an important role in the initial stage of triggering the bone defects repair. The combination of bioactive small molecule drugs and biomaterials has been a powerful strategy for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The tensile test also showed that the tensile strength of the hydrogel could reach 23 kPa, and the elongation rate was 160% after photocrosslinking. Due to the reinforcement of nanoparticles, , after the introduction of PDA nanoparticles, the tensile strength of the hydrogel was increased to 33 kPa, and the elongation ratio was increased to 220% (Figure d). In addition, the PS 12 -OSA 1 -P 0.03 hydrogel showed highly overlapping curves in the cyclic loading–unloading test, with a small hysteresis loop, and exhibited a high elasticity (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…The tensile test also showed that the tensile strength of the hydrogel could reach 23 kPa, and the elongation rate was 160% after photocrosslinking. Due to the reinforcement of nanoparticles, , after the introduction of PDA nanoparticles, the tensile strength of the hydrogel was increased to 33 kPa, and the elongation ratio was increased to 220% (Figure d). In addition, the PS 12 -OSA 1 -P 0.03 hydrogel showed highly overlapping curves in the cyclic loading–unloading test, with a small hysteresis loop, and exhibited a high elasticity (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…In chemical reaction method, the functional groups in the molecular chain of a polymer react with each other to form covalent bonds; examples include the thiololefn click reaction [ 100 ], Schiff base reaction [ 78 ], free-radical polymerization [ 101 ], and hybridization chain reaction [ 31 ]. A gel formed by chemical crosslinking has higher mechanical properties and no melting or dissolving.…”
Section: Crosslinking Methods Of Mesoporous Material-loaded Composite...mentioning
confidence: 99%
“…Carboxylated mesoporous silica loaded into a gelatin methacryloyl hydrogel not only increased the mechanical strength, compressive modulus, and swelling ratio of the hydrogel, but also led to a controlled release of metformin, endowing the hydrogel with better biocompatibility, antibacterial activity, and superior stem cell adhesion and proliferation induction [ 77 ]. The alginate/chitosan polyelectrolyte-modified mesoporous silica nanoparticles also improved the mechanical properties of aldehyde hyaluronic acid/N, O-carboxymethyl chitosan hydrogels and achieved sustained drug release due to the Schiff base reaction between the aldehyde group in aldehyde hyaluronic acid and the amino group in chitosan [ 78 ].…”
Section: Classification Of Mesoporous Material-loaded Composite Hydro...mentioning
confidence: 99%
“…ELISA 4,97,115,168 28.6% HPLC 120 7.1% Weight measurements of drug 106 7.1% Drug specific testing BCA protein assay−used commonly for BSA loading 92,130 14.3%…”
Section: 7%mentioning
confidence: 99%